Children and disability in the age of sharenting. The "right to an open future" as a principle for an ethical evaluation - Scalzaretto, Silvia (Medicina e Morale, 2023)
The phenomenon of parents sharing every aspect of their children's lives on social media is now so common and widespread enough that a specific term has been coined for it, a neologism that derives from the crasis of the terms "share" and "parenting": sharenting. This word focuses on cases where the life of a child with illness or disability is shared in a constant and massive way. While it is true that there are often positive aspects that lead parents to act in this way (such as being an inspiration or motivation for others, promoting social acceptance of the disease, building a network in order to support, raising funds) these criteria are mostly declared by the parents themselves, but not actually verified or demonstrated and in some cases they have been openly denied. In any case, what emerges is that the adult tends to provide his own narrative and interpretation of the disease (or rather, of his own care relationship), a narrative that the child has no voice to control. This narrative, in addition to openly harming the minor's privacy, creates an indissoluble connection between the child and his condition, making his identity inseparable from the disease and not allowing him to have an identity free from the disease in the future. On the assumption that the minor's right to health has a content that does not coincide with the adult's perspective and story and also necessarily must include future prospects, the classic criteria of ethical analysis may not be exhaustive. In this paper I will try to apply the principle theorized by Joel Feinberg on the right of the child to an "open future" as a criterion to identify the limits of what is ethically acceptable to share online. The study does not in any way intend to demonize technologies, nor obviously to prevent or limit them; it aims to promote a responsible use of them, also reminding to never forget the fundamental need to protect the most vulnerable subjects.